So you want to sing musical theatre : a guide for performers - Flynn, Amanda (So you want to sing., 2022)
"Broadway vocal coach, voice teacher, and researcher Amanda Flynn provides the skills singers need to successfully sing musical theatre repertoire. The book is updated and expanded for musical theatre performance in the current era, covering a broader array of topics and including more in-depth discussion than the original edition"--